Backstepping Control Under Multi-Rate Sampling - Tanasa, Valentin; Monaco, Salvatore; Normand-Cyrot, Dorothee (IEEE transactions on automatic control, 2016)
The paper deals with the design of sampled-data controllers which preserve the stabilizing performance of a continuous-time backstepping control strategy. This is achieved through matching of the control Lyapunov functions evolutions at the sampling instants. The method is developed for systems in strict-feedback form. The results are discussed and compared with similar strategies through simulated examples.